Degradation of Deepwater Horizon oil buried in a Florida beach influenced by tidal pumping. (January 2018) - Huettel, Markus; Overholt, Will A.; Kostka, Joel E.; Hagan, Christopher; Kaba, John; Wells, Wm. Brian; Dudley, Stacia
Abstract: After Deepwater Horizon oil reached the Florida coast, oil was buried in Pensacola Beach (PB) sands to ~ 70 cm depth, resulting in Total Petroleum Hydrocarbon (TPH) concentrations up to ~ 2 kg per meter of beach. This study followed the decomposition of the buried oil and the factors influencing its degradation. The abundance of bacteria in oiled sand increased by 2 orders of magnitude within one week after oil burial, while diversity decreased by ~ 50%. Half-lives of aliphatic and aromatic hydrocarbons reached 25 and 22 days, respectively. Aerobic microbial oil decomposition, promoted by tidal pumping, and human cleaning activities effectively removed oil from the beach. After one year, concentrations of GC-amenable hydrocarbons at PB were similar to those in the uncontaminated reference beach at St. George Island/FL, and microbial populations that disappeared after the oil contamination had reestablished. Yet, oxihydrocarbons can be found at PB to the present day. Graphical abstract: Tidal pumping enhanced buried oil degradation in Gulf of Mexico sandy beaches through improving environmental conditions for microbial degradation in the sand and removal of degradation products. During ebb tide, warm O2 -saturated air was drawn into the sand supporting aerobic microbial oil degradation in deeper sediment layers. During flood, air was pumped upward through the oiled sand, providing moisture for sedimentary microbial growth and removing CO2 from the beach. Highlights: Oil found buried 70 cm deep in Florida sandy beach after Deepwater Horizon spill. Buried oil triggered blooms of oil-degrading bacteria and a microbial succession. Tidal pumping enhanced gas exchange and aerobic oil degradation. Human cleaning activities and microbial oil degradation led to a rapid beach recovery.